NEPOTISM, FAVORITISM AND CRONYISM: A STUDY OF THEIR EFFECTS ON JOB STRESS AND JOB SATISFACTION IN THE BANKING INDUSTRY OF NORTH CYPRUS - Arasli, Huseyin; Tumer, Mustafa (Soc Personality Res Inc, 2008)
Nepotism, cronyism and favoritism are unprofessional practices giving preferential treatment to relatives and friends in employment. For this study a survey was carried out with 576 respondents working in the banking industry in northern Cyprus. An analysis was then conducted to assess the impact of these practices on job stress, job satisfaction, and intention to quit behavior of employees, as well as word of mouth comments in their workplaces. Results of this study show that nepotism, favoritism and cronyism create job stress in the workplace and this increases dissatisfaction of the staff about their organizations. Nepotism has the greatest negative effect on job stress.
Keywords: nepotism; favoritism; cronyism; banking industry; Cyprus